PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUASAN MELALUI KEPUTUSAN PEMBELIAN DI LTG BY ESTERAKYAT - Andri Setiawan; Rivera Pantro Sukma Silitonga (LPPM Universitas Asa Indonesia, 2023)
The purpose of this research is to determine the effect of product quality, promotion on customer satisfaction through purchasing decisions at LTG by Esterakyat. Researchers used purposive sampling method to select respondents. The number of samples for this study consisted of 200 respondents. Data collection was carried out using a questionnaire that had been tested for validity and reliability. the sampling technique used in this research method is purposive sampling technique. hypothesis testing using path analysis with the help of Smart PLS 3.0. the results of this study indicate that product quality has a positive and significant effect directly or indirectly on customer satisfaction through purchasing decisions but on the other hand, promotion has no direct or indirect effect on customer satisfaction through purchasing decisions.